Cervical Carcinoma: Current Role of Laparoscopy - Stefan Rimbach (European Medical Journal, 2015)
This review aims to analyse and describe the current role of laparoscopy in the treatment of cervical cancer. Laparoscopy has become an important tool in gynaecological oncology. Its general advantages in comparison with open surgery apply to oncological patients as much as they do to benign conditions. Data from retrospective and case-control studies have proven that treatment of early cervical carcinoma is successfully feasible by means of minimally invasive surgery with no compromise of oncological principles nor radicality. Thus, laparoscopy has entered guideline recommendations as an alternative to open procedures when operative therapy is indicated. Nevertheless, laparoscopic radical hysterectomy, as well as lymphadenectomy, remain demanding and require surgeons experienced in both operative oncology and endoscopy.